2016
DOI: 10.5194/isprs-archives-xli-b4-653-2016
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art of 3d National Mapping in 2016

Abstract: ABSTRACT:Techniques for 3D mapping are maturing. At the same time the need for 3D data is increasing. This has pushed national (and regional) mapping agencies (NMAs) to consider extending their traditional task of providing topographic data into the third dimension. To show how research results in 3D mapping obtained over the past twenty years have been adopted by practice, this paper presents the ongoing work on 3D mapping within seven NMAs, all member of the 3D Special Interest Group of European Spatial Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Hence, the reference model (BIM-CAREM) for controlling the BIM competence of AEC/FM processes, consists of two parts which are the BIM process reference model and the BIM measurement framework (Yilmaz et al 2019). Unfortunately, there are no standard approaches to measure the 3D model calculated from Lidar data quality (Stoter et al 2016 andWong andEllul 2016). Moreover, the absence of Lidar data and BIM regulations was the motivation for suggesting the employment of the Lidar data evaluation concept in the procedure of developing a 3D-BIM model based on Lidar point clouds (Warchol 2019).…”
Section: Related Workmentioning
confidence: 99%
“…Hence, the reference model (BIM-CAREM) for controlling the BIM competence of AEC/FM processes, consists of two parts which are the BIM process reference model and the BIM measurement framework (Yilmaz et al 2019). Unfortunately, there are no standard approaches to measure the 3D model calculated from Lidar data quality (Stoter et al 2016 andWong andEllul 2016). Moreover, the absence of Lidar data and BIM regulations was the motivation for suggesting the employment of the Lidar data evaluation concept in the procedure of developing a 3D-BIM model based on Lidar point clouds (Warchol 2019).…”
Section: Related Workmentioning
confidence: 99%
“…These plans are implemented as part of the project Public Administration Center for Spatial Analysis CAPAP organised by the Polish Head Office of Geodesy and Cartography (Stoter et al, 2016;Pilarska et al, 2017). This project provides a range of products and services related to spatial data, including 15 million of buildings in LOD2 standard based on the ALS elevation data and the building footprint from the topographic database BDOT10K.…”
Section: Capap Projectmentioning
confidence: 99%
“…Several studies have conducted different forms of requirements analysis of 3D data (Biljecki et al, 2015;Sargent et al, 2015;Stoter et al, 2013;Stoter et al, 2016;Walter, 2014;Wong and Ellul, 2017) -more details on these studies can be found in Wong and Ellul (2017). Two key points emerge from these studies.…”
Section: D Data Requirements Gatheringmentioning
confidence: 99%